2009
DOI: 10.3748/wjg.15.5712
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ONO-4057 and tacrolimus on ischemia-reperfusioninjury of the liver

Abstract: AIM:To investigate the effects of a novel Leukotriene B4 receptor antagonist and/or tacrolimus on ischemiareperfusion in a rat liver model. METHODS:Male Lewis rats were pretreated with ONO-4057 (100 mg/kg) and/or tacrolimus (1 mg/kg) orally, and divided into four experimental groups; group 1 (control), group 2 (ONO-4057), group 3 (tacrolimus), group 4 (ONO-4057 + tacrolimus). RESULTS:There was a tendency for long survival in the groups treated with tacrolimus alone and ONO-4057 plus tacrolimus. Post-reperfusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 18 publications
0
4
0
2
Order By: Relevance
“…Rats were daily treated orally using an adopted dull needle (intragastric gavage) with one of the examined ISD in the low (LD) or high (HD) dose ( n = 9) for 14 days (Table 3). Low and high doses according to the therapeutic doses were used in rat‐model transplantation [8–12]. The dosages used in rats are higher than those used in humans because of a different body area to volume ratio and a much faster hepatic metabolism.…”
Section: Methodsmentioning
confidence: 99%
“…Rats were daily treated orally using an adopted dull needle (intragastric gavage) with one of the examined ISD in the low (LD) or high (HD) dose ( n = 9) for 14 days (Table 3). Low and high doses according to the therapeutic doses were used in rat‐model transplantation [8–12]. The dosages used in rats are higher than those used in humans because of a different body area to volume ratio and a much faster hepatic metabolism.…”
Section: Methodsmentioning
confidence: 99%
“…It was clear that these two (2) drugs ameliorated graft viability. And Takeichi T, et al reported that pretreatment with ONO-4057 (Leukotriene B4 receptor antagonist) in combination with tacrolimus produced additive effects in a rat model of liver IRI (38).…”
Section: Discussionmentioning
confidence: 99%
“…Прирост уровня IL-17 между пробами крови печеночных вен во время ТП и на 1-е п/о сутки в группах с инфузией и без инфузии такролимуса в воротную вену и печеночную артерию во время back-table-операции No Yes Tacrolimus back-table IL-1 increment, pg/ml ОБСУЖДЕНИЕ Теоретическое обоснование фармакологической гепатопротекции лежит в необходимости ослабления ИРП как причины РДТ при трансплантации печени. Результаты экспериментальных исследований системного применения такролимуса показали его эффективность в отношении ИРП печени [10][11][12]. Несколько возможных механизмов гепатопротекции при ИРП и ТП известны при использовании такролимуса.…”
Section: серологические маркерыunclassified
“…Экспериментальные данные свидетельствуют о потенциальной роли ингибитора кальциневрина такролимуса в ослаблении ИРП и гепатопротекции при ТП [10][11][12]. Было показано, что такролимус способен угнетать воспаление и иммунный ответ в трансплантированной печени на геномном уровне, а также имеются данные о протективной функции ингибиторов кальциневрина при ИРП сердца, что свидетельствует об органо-неспецифическом возможном механизме действия [13,14].…”
Section: Introductionunclassified